Unilateral magnetic resonance-guided focused ultrasound for medication-refractory essential tremor: 5-year continued access study - Ghanouni, Pejman; Krishna, Vibhor; Eisenberg, Howard M.; Elias, W. Jeffrey; Cosgrove, G. Rees; Gwinn, Ryder; Kaplitt, Michael G.; Baltuch, Gordon H. (Frontiers in Neurology, 2025)
BackgroundEssential tremor (ET) is a common neurologic disorder, with 30–50% of patients experiencing medication-refractory symptoms. Magnetic resonance-guided focused ultrasound (MRgFUS) thalamotomy is an approved, effective treatment for medication-refractory ET. In this open-label, continued access study, subjects were enrolled prospectively after the pivotal MRgFUS trial completed enrollment, but before US Food and Drug Administration approval. The objective of this study was to evaluate the long-term (5-year) effectiveness and safety of unilateral MRgFUS thalamotomy in medication-refractory ET patients.MethodsEffectiveness was evaluated by change from baseline in Clinical Rating Scale for Tremor (CRST) scores and quality of life (QoL) with the Quality of life in Essential Tremor (QUEST) questionnaire. Adverse events (AEs) following MRgFUS thalamotomy were recorded. Observed data were utilized for the main analysis. Sensitivity analyses using last observation carried forward and best-worst case scenarios were completed to evaluate the impact of missing data at long-term visits.ResultsOf 61 treated subjects, the mean (SD) age was 69.5 (14.0) years, most (67.2%) were male, and 26 (42.6%) were observed for 5 years. MRgFUS thalamotomy improved tremor/motor function (CRST Parts A and B), tremor severity (postural component of CRST Part A for the treated side), and functional disability (CRST Part C) scores throughout the study. At 1- and 5-year follow-up, respective percentage improvements from baseline were: tremor/motor function, 62.2% and 51.9%; tremor severity, 75.6% and 67.4%; and functional disability, 65.4 and 35.4%. QoL improved by 53.6 and 43.7% at 1- and 5-year follow-up, respectively. Almost all related AEs were mild (85%) or moderate (12%) in severity, with 3% being severe. More than half of related events resolved in 6 months.ConclusionMRgFUS thalamotomy is a safe and effective long-term treatment for patients with medication-refractory ET and is associated with improved QoL.